Karakterisasi sistem pembangkit aliran elektrohidrodinamika lucutan korona positif berkonfigurasi elektroda kawat-bidang - Sumariyah Sumariyah; Azzuma Hasna Azzulkha; Muhammad Nur; Zaenul Muhlisin (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
The characterization of electrohidrodynamic flow generation system (EHD) has been performed utilizing positive corona discharge configured wire-plate electrode. In this study, the characteristics of the EHD flow generation system in the form of current characteristics as a function of voltage or I-V characteristics with fixed geometry factor, in the without of lubricating oil and with the lubricating oil. The fixed geometry factor was obtained from the radius of the fixed point (r) electrode with various the electrode distance (d). This research was conducted by using positive corona incandescent discharges with wire field electrode configuration. The wire electrode used is made of stainless steel having a length of 5 cm, with wire diameter 0.11 mm, 0.14 mm, 0.21 mm, 0.36 mm, and 0.38 mm. Electrode of field used in the form of circle with diameter 20 cm. Data collection system with variation of voltage, variation of electrode distance, and variation of wire electrode diameter used. Furthermore, data analysis of measurement results was carried out. From the result of characteristic research of EHD flow generator system in the form of current as a function of voltage shows that the increase of voltage is proportional to current increase. While the current as a function of geometry shows the value of the current flowing inversely proportional to the geometry factor of the electrode distance change.Keywords:electrohydrodinamic, ion wind, positive corona discharge